Pengembangan Aplikasi Mentimeter Berbasis Artificial Intelligences sebagai Implementasi Revolusi Industri 5.0 - Wijayanti, Reli -; Firdaus, Riril Mardiana; Yudiono, Udik (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2025)
Industry Revolution 5.0 is a process of implementing advanced technology in conjunction with human expertise to develop an education system that is more responsive to the changing times. This research was conducted as a solution to address the issue of active student involvement in the classroom. The objectives of this study are: 1) to design the development of an AI-based Mentimeter application, and 2) to assess the feasibility, practicality, and appeal of the AI-based Mentimeter application in the Digital Business Expertise Concentration subject, particularly in the fields of business economics and general administration. This study uses the Research and Development (R&D) method to produce a product in the form of an animated video utilizing the AI-based Mentimeter application. The development model applied is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The study involved 31 students from the Digital Business program, 2 course instructors, 3 subject matter experts (validators) in content, media, and language, as well as 1 teacher as the product user. The techniques used for data collection include observation to gather information and data on the issues faced by teachers in creating interactive learning media, validation surveys from content, media, and language experts, teacher feedback, testing with a small group, and testing with a large group. The results of the study indicate that: 1) The design of the learning media using the AI-based Mentimeter application, with the output being an animated video that is easily accessible to students; 2) The validation results of the AI-based Mentimeter application development by content, media, and language experts show excellent results. Feedback from Digital Business subject teachers was rated as very good. Similarly, feedback from students regarding the appeal of the AI-based Mentimeter application product was also rated as very good. Therefore, the animated video developed was proven to be valid, practical, and engaging for use in Digital Business Expertise Concentration learning.